Experimental Acupuncturology (Springer Singapore, 2018)
This book focuses on the use of acupuncture as a possible and alternative treatment in analgesia, drug addiction, depression, itchiness, peripheral nerve regeneration, stroke, diabetes, cognitive deficits and sleep regulation. Formal recognition by WHO and UNESCO concerning the use and efficacy of acupuncture science in modern medicine has encouraged high levels of investment and commitment to research and development activities into acupuncture science from several top-level health science research and treatment institutes in China Mainland, Taiwan, Japan, Korea, France and the USA. This book aims to provide direction and guidance on how the medical community can proceed with acupuncturology in modern medical treatment and precision medicine.